Reaching the right farmers: targeting key customer segments for certified sweetpotato seed in Uganda - Namazzi, S.; Rajendran, S.; Omongo, C. (2025)
This study segmented Ugandan sweetpotato farmers into three distinct customer profiles to guide marketing and distribution of certified seed. Conducted across four agroecological zones with 87 clean-seed buyers, the research identified three key customer segments: Business-Oriented (45%), Climatarians (32%), and Inspired (23%). Each group displayed unique motivations—profitability, climate resilience, and peer influence, respectively. Tailored marketing approaches were developed for each: ROI-based campaigns and digital outreach for the Business-Oriented, climate-resilient messaging and radio promotions for the Climatarians, and storytelling and recognition programs for the Inspired group. The findings show that farmer adoption is driven by visible results, trust, and peer learning. The brief recommends applying behavioral segmentation to design inclusive, profitable, and climate-smart seed systems.